Population Fluctuations Of Root Mealy Bug, Paraputo Sp. (Hemiptera: Pseudococcidae), – A Dreaded Pest Of Mulberry In Darjeeling Hills Of West Bengal (India) (Applied Biological Research, 2013)
Root mealy bug Paraputo sp. (Hemiptera: Pseudococcidae) is the most dreaded  pest of mulberry (Morus sp.), in Darjeeling hills of West Bengal (India). The  pest incidence recorded at monthly intervals for three consecutive years revealed that the pest population was low in December-January, increased with  rise in temperature and relative humidity upto rainy season (July-August) and  then gradually declined. The peak population of 50.88-52.05 plant-1 was in  August. No significant variation was observed between the years in population  fluctuations.
Keywords: Darjeeling hills; mulberry; pest; population fluctuations; root mealy bug; silkworm